Robert B. Parker's Colorblind [compact disc, unabridged] - Coleman, Reed Farrel, 1956- (Parker, Robert B., 1932-2010. Jesse Stone novel (Audio)., 2018)
Jesse Stone is back on the job after a stint at rehab, and the road to recovery is immediately made bumpy by a series of disturbing and apparently racially motivated crimes, beginning with the murder of an African-American female tourist. Then, Jesse's own deputy Alisha, the first black woman to join the police force in Paradise's history, becomes the target of a sophisticated frame-up. As he and his team work tirelessly to unravel the truth, he has to wonder if this is just one part of an even grander plot, one with an end game more destructive than any of them can imagine.